Interventions to Reduce Medication Dispensing, Administration, and Monitoring Errors in Pediatric Professional Healthcare Settings: A Systematic Review - Koeck, Joachim A.; Young, Nicola J.; Kontny, Udo; Orlikowsky, Thorsten; Bassler, Dirk; Eisert, Albrecht (Frontiers in Pediatrics, 2021)
Introduction: Pediatric patients cared for in professional healthcare settings are at high risk of medication errors. Interventions to improve patient safety often focus on prescribing, however the subsequent stages in the medication use process (dispensing, drug administration and monitoring) are also error prone. This systematic review aims to identify and analyze interventions to reduce dispensing, drug administration and monitoring errors in professional pediatric healthcare settings. Methods: Four databases were searched for experimental studies with separate control and intervention groups, published in English between 2011-2019. Interventions were classified for the first time in pediatric medication safety according to the ‘Hierarchy of Controls’ model, which predicts that interventions at higher levels are more likely to bring about change. Higher level interventions aim to reduce risks through elimination, substitution or engineering controls. Examples of these include the introduction of smart pumps instead of standard pumps (a substitution control) and the introduction of mandatory bar-code scanning for drug administration (an engineering control). Administrative controls such as guidelines, warning signs and educational approaches are lower on the hierarchy and therefore predicted by this model to be less likely to be successful. Results: Twenty studies met the inclusion criteria, including 1 study of dispensing errors, 7 studies of drug administration errors, and 12 studies targeting multiple steps of the medication use process. A total of 44 interventions were identified. Eleven of these were considered higher level controls (4 substitution and 7 engineering controls). The majority of interventions (n=33) were considered ‘administrative controls’ indicating a potential reliance on these measures. Studies which implemented higher level controls were observed to be more likely to reduce errors, confirming that the ‘Hierarchy of controls’ model may be useful in this setting. Heterogeneous study methods, definitions and outcome measures meant that a meta-analysis was not appropriate. Conclusions: When designing interventions to reduce pediatric dispensing, drug administration and monitoring errors, the ‘Hierarchy of controls’ model should be considered, with a focus placed on the introduction of higher level controls, which may be more likely to reduce errors than the administrative controls often seen in practice.